Development of high toughness cermets for applications in tool and aerospace industries - Zhang, Sam (2008)
This research concentrated on the development of high toughness cermet by applying PSSS treatment and changing the composition of the materials, especially the composition of the binder phase. Ceramic powders of Ti(CN), TaC, WC were mixed, compacted and heat-treated at high temperatures to form (Ti, W, Ta)(C, N) solid solution, which was then ball-milled to fine powders before mixing with metallic binder and compacted.